The enabling environment for disaster risk financing in Pakistan country diagnostics assessment. (Asian Development Bank, 2019)
This publication seeks to strengthen financial preparedness for disasters in Pakistan, focusing on insurance and other risk transfer instruments. It also explores the current application of disaster risk financing solutions by the government, businesses, and individual households; related demand and supply constraints; and opportunities for improvement. This is one of a series of country diagnostics assessments that used a common methodology to determine the state of the enabling environment for disaster risk financing.